Identifying key clinical markers for congenital cytomegalovirus infections: a PCR-confirmed case-control study - Corebima, Brigitta IRV; Iskandar, Agustin; Sulistijono, Eko; Amalia, Najwa; Fauziah, Dina; Sanjaya, Hayyu Rafina (Paediatrica Indonesiana, 2025)
Background Congenital cytomegalovirus (CCMV) infection is the leading cause of congenital infections worldwide. Clinical manifestations of CCMV are highly variable and make the clinical diagnosis difficult, especially in settings where advanced diagnostic tools are not available. Objective To identify a cluster of clinical manifestations indicative of CCMV and analyze for correlations with PCR-confirmed diagnoses. Methods This case-control study was conducted at a tertiary care hospital in Malang, East Java, and included 40 neonates clinically suspected to have CCMV. PCR specimens from urine or saliva were collected and analyzed to evaluate clinical manifestations of suspected CCMV. Demographic and clinical data were organized and analyzed using SPSS. Results Of neonates with suspected CCMV, 32.5% (n=13) had PCR-confirmed CCMV. The median age for PCR testing post-suspected CCMV was 8.50 (range 3.75 to 24.25) days. Significant correlations emerged between PCR-confirmed CCMV and symptoms such as microcephaly, jaundice, purpura, thrombocytopenia, acute liver injury, hepatomegaly, feeding difficulties, and anemia. However, seizures, low birth weight, ventriculomegaly, and intrauterine growth restriction did not show significant associations, indicating their limited utility as solitary markers for CCMV. The clinical symptoms associated with CCMV were confirmed by PCR, emphasizing the significance of certain sign and symptom clusters, such as microcephaly with thrombocytopenia (OR 41.60; P<0.001), or the traditional triad of jaundice, purpura, and hepatosplenomegaly/acute liver injury (OR 41.60; P<0.001). Conclusion Several clinical manifestations are significantly associated with PCR-confirmed CCMV infection, underscoring the diagnostic value of specific symptom combinations in identifying CCMV infection. These combinations are microcephaly and thrombocytopenia and the classic triad of jaundice, purpura, and hepatosplenomegaly/acute liver injury.